1992
DOI: 10.1128/iai.60.4.1509-1513.1992
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of oocyst wall and sporozoite antigens from three Cryptosporidium species

Abstract: A comparison was made of the antigenic composition of oocyst walls and sporozoites from Cryptosporidium baileyi from turkeys, C. muris from rodents, and C. parvum from ruminants, employing immunoblotting and immunofluorescence. In immunoblotting, oocyst antigens were subjected to sodium dodecyl sulfate-polyacrylamide gel electrophoresis and Western blotting (immunoblotting) and detected with rabbit polyclonal anti-C. muris or-C. parvum antibodies or murine monoclonal antibodies developed against C. parvum. Imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 20 publications
0
9
1
Order By: Relevance
“…When antigens obtained from C. muris oocysts and sporozoites are used in immunoblotting, bands at 110 kDa, 54-51 kDa, and in the region of low molecular weights have been found (Nina et al, 1992) , unlike our finding of sporozoite antigens with bands at 78, 47.5, and 27.5 kDa. C. parvum sporozoites have surface antigens of 55, 28, 20, and 15 kDa that may be responsible for induction of the neutralization antibodies (Mead et al, 1988;Riggs et al, 1989;Tilley et al, 1991) .…”
Section: Infectivity Of Sporozoites Treated With Antiserumcontrasting
confidence: 97%
“…When antigens obtained from C. muris oocysts and sporozoites are used in immunoblotting, bands at 110 kDa, 54-51 kDa, and in the region of low molecular weights have been found (Nina et al, 1992) , unlike our finding of sporozoite antigens with bands at 78, 47.5, and 27.5 kDa. C. parvum sporozoites have surface antigens of 55, 28, 20, and 15 kDa that may be responsible for induction of the neutralization antibodies (Mead et al, 1988;Riggs et al, 1989;Tilley et al, 1991) .…”
Section: Infectivity Of Sporozoites Treated With Antiserumcontrasting
confidence: 97%
“…Furthermore, some C. parvum isolates have been shown to infect chicks when large numbers of oocysts are used for inoculation (20,34). The results of an analysis of an undefined DNA sequence (39) and an antigen reactivity analysis (23) also suggested that C. parvum and C. baileyi are more closely related to each other than they are to C. muris. The results of this study also suggest that Cryptosporidium parasites are not related to other coccidians at the SSU rRNA locus.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of an efficient in vitro culturing system for this parasite (5) still represents a serious obstacle to understanding the biology of the parasite and to studying the immunological and biochemical properties of Cryptosporidium antigens. In fact, until recently, few parasite proteins have been extensively characterized (1,(14)(15)(16) and very few genes have been cloned (4,6,9). There is an urgent need to collect more information on the biology of Cryptosporidium proteins.…”
mentioning
confidence: 99%